Fish otolith microchemistry as a biomarker of the world's largest mining disaster - Daros, Felippe Alexandre [UNESP]; Condini, Mario Vinicius; Altafin, Julia Pohl [UNESP]; de Oliveira Ferreira, Franklin [UNESP]; Hostim-Silva, Maurício (Elsevier, 2022)
The Fundão dam collapse occurred in late 2015, resulting in the largest disaster in the world involving mine tailings, releasing at least 50 million m3 of iron ore tailings into the Doce river basin (Brazil). Studies realized along the Doce river after the disaster showed high concentrations of some elements above recommended Brazilian standards in different environmental matrices such as Al, Ba, Co, Fe, Hg, Mn, and Ni. This study aims to test the hypothesis that otolith microchemistry can be used as a pollution biomarker over time, that is, the otoliths sampled in the directly impacted area (Doce estuary) will present higher concentrations of the chemical elements in relation to the two other indirectly impacted estuaries (Ipiranga and São Mateus). The marine catfish Genidens genidens was chosen as a sentinel species, as this species presents several features that characterize it as a key species of the estuarine environment. The hypothesis was tested from a comparison between estuaries of the element/Ca ratios (Ba, Fe, and Mn) from the otolith edge (representing more recent deposition) and through the elemental composition profile, from core to edge of otolith. For the otolith edge analyses, it was possible to determine significant differences between estuaries in all three element:Ca ratios (Ba, Fe, and Mn). For the profile analysis (from core to edge), the Doce river showed consistent concentrations of Fe:Ca and Ba:Ca ratios higher than those of the Ipiranga and São Mateus estuaries throughout the life of the fish. In otoliths sampled in the Doce estuary, the possible identified peak of the Ba:Ca and Mn:Ca ratios, was probably associated with the Fundão Dam disaster. The present study showed that otolith microchemistry can be used as a sclerochronological biomarker of metallic aquatic pollution.
Keywords: Aquatic pollution; Estuarine environment; Fundão dam's; Sclerochronological